A budget analysis of the formation of haze in Beijing. (January 2015) - Tie, Xuexi; Zhang, Qiang; He, Hui; Cao, Junji; Han, Suqing; Gao, Yang; Li, Xia; Jia, Xing Chan
Abstract: During recent winters, hazes often occurred in Beijing, causing major environmental problems. To understand the causes of this "Beijing Haze", a haze episode (from Oct. 21 to Oct. 31, 2013) in Beijing was analyzed. During the episode, the daily mean concentration of fine particulate matter (PM2.5 ) reached a peak value of 270 μg/m 3 on Oct. 28, 2013, and rapidly decreased to 50 μg/m 3 the next day (Oct. 29, 2013). This strong variability provided a good opportunity to study the causes of a "Beijing Haze". Two numerical models were applied for this study. The first model is a chemical/dynamical regional model (WRF-Chem). This model is mainly used to study the effects that weather conditions have on PM2.5 concentrations in the Beijing region. The results show that the presence of high air pressure in northwest Beijing (NW-High) generally produced strong northwest winds with clean upwind air. As a result, the NW-High played an important role in cleaning Beijing's PM. However, the NW-High's cleaning effect did not occur in every situation. When there was low air pressure in southeast Beijing (SE-Low) accompanied by an NW-High, an air convergent zone appeared in Beijing. The pollutants became sandwiched, producing high PM2.5 concentrations in the Beijing region. The second model used in this study is a box model, which is applied to estimate some crucial parameters associated with the budget of PM2.5 in the Beijing region. Under calm winds, the calculations show that continuous local emissions rapidly accumulate pollutants. The PM2.5 concentrations reached 150 μg/m 3 and 250 μg/m 3 within one (1) day and two (2) days, respectively. Without horizontal dilution, this estimate can be considered as an upper time limit (the fastest time) for the occurrences of haze events in the Beijing region. The wind speed (WSb ) is calculated for the balance between the continuous emissions and atmospheric clean processes. The results show that the WSb is strongly dependent on the planetary boundary layer (PBL) height and the wind direction. Under SE-Low weather conditions, the WSb is 2 m/s with a higher PBL height (700 m). However, under lower PBL heights, the WSb rapidly increases, reaching 4.5 m/s and 7.0 m/s with PBL heights of 300 m and 200 m, respectively. In contrast, under NW-High weather conditions, the WSb reduces to 2.5 m/s and 4.0 m/s. These results suggest that when the prevailing wind in Beijing is a northwest wind (with wind speeds of >4 m/s), particulate matter (PM) begins to decrease. Highlights: A haze episode with a very strong variability in Beijing was analyzed. WRF-Chem and a box model are used for the budget analysis of haze formation. Under calm winds, a heavy haze can be formed in one (1) day. The wind speed to balance emission-clean processes was calculated.